2023
DOI: 10.3390/microorganisms11041081
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Lyme Borreliosis in The Netherlands: A Population-Based Cross-Sectional Study

Abstract: Lyme borreliosis (LB) is not notifiable in many European countries, and accurate data on the incidence are often lacking. This study aimed to determine the seroprevalence of Borrelia burgdorferi sensu lato (s.l.)-specific antibodies in the general population of The Netherlands, and to determine risk factors associated with seropositivity. Sera and questionnaires were obtained from participants (n = 5592, aged 0–88 years) enrolled in a nationwide serosurveillance study. The sera were tested for B. burgdorferi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The overall incidence rate in Poland was estimated as 53.7 in 2019 [6]. In the current study, the seroprevalence was higher among men compared to women and increased with the age of participants, which is in accordance with studies of the general population of The Netherlands [30] and most of the studies in European countries, as demonstrated in the review paper by Burn et al [31]. In turn, LB cases were more common among women (55.7%) than men during 2015-2019 in Poland [32].…”
Section: Discussionsupporting
confidence: 90%
“…The overall incidence rate in Poland was estimated as 53.7 in 2019 [6]. In the current study, the seroprevalence was higher among men compared to women and increased with the age of participants, which is in accordance with studies of the general population of The Netherlands [30] and most of the studies in European countries, as demonstrated in the review paper by Burn et al [31]. In turn, LB cases were more common among women (55.7%) than men during 2015-2019 in Poland [32].…”
Section: Discussionsupporting
confidence: 90%